Impact of COVID -19 on Healthy Life of People in India - Awasthi, Aishwarya; Singh, Shivendra Kumar (Indian Journal of Community Health, 2023)
The COVID-19 pandemic is not the first, and certainly not the last, to strike the world. COVID-19 has conjointly been a serious concern in higher-income countries, with several European countries and over eleven million individuals in the Republic of India had been infected with COVID-19. Though some countries and regions are seeing improvements in hospitalization and death rates, COVID-19 remains a significant concern for vulnerable and underserved populations globally. The COVID-19 pandemic is unexampled and heavy, and numerous of the policy measures taken to mitigate and contain it were necessary and comprehensible. Factors associated with difficulty in accessing medicine due to the COVID-19 situation With the diversion of human resources to COVID-19 work, active case finding for TB has been postponed by a number of states in India. Though regulative authorities in many countries have approved one or a lot of COVID-19 vaccines for emergency use, necessary challenges remain in mass manufacturing and distributing vaccines in developing countries. The national authorities need to arrange for the challenges associated with the health of their population coincidental with combating the COVID-19 pandemic. It's unclear, however, whether the twin impacts of COVID-19 and also the health care disruptions have an effect on these people within the semi-permanent.